2016
DOI: 10.18203/issn.2455-4510.intjresorthop20160708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diagnostic features of osteoarthrosis of the temporomandibular joint: a review

Abstract: Temporomandibular disorders (TMD) consist of not only the internal derangement of Temporomandibular joint (TMJ) but also areas extrinsic to TMJ. Osteoarthritis is a common degenerative joint disease that manifests as a chronic debilitating disease and occurs due to degradation and loss of articular cartilage. There occur changes in the subchondral bone and other soft tissues. Osteoarthritis is not uncommon in the Temporomandibular joints (TMJs). The etiopathogenesis of osteoarthritis is associated with multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
(24 reference statements)
0
12
0
1
Order By: Relevance
“…The main symptom of an arthritic joint is dull pain. The inflammatory clinical features of the disease also include: masticatory muscles and TMJ tenderness, joint instability, stiffness, joint sounds and decreased range of joint motion (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The main symptom of an arthritic joint is dull pain. The inflammatory clinical features of the disease also include: masticatory muscles and TMJ tenderness, joint instability, stiffness, joint sounds and decreased range of joint motion (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Temporomandibular joint osteoarthritis (TMJ‐OA) is a subtype of temporomandibular disorders (Zarb and Carlsson, ), characterized by progressive cartilage degradation, subchondral bone remodelling, and chronic inflammation of the synovial tissue (Bansal, ; Wang, Zhang, Gan, & Zhou, ). The exact pathogenesis of degenerative changes of TMJ remains unclear, due to the several high risk factors probably involved (Alanen, ; Bansal, ; Wang et al, ). Numerous studies suggested that TMJ‐OA is mainly related to oral health.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses in current (e.g., Bertram et al, ; Eversole, Pappas, & Graham, ; Takayama, Miura, Yuasa, Kobayashi, & Hosoi, ) and ancient (e.g., Hinton, ; Hinton & Carlson, ; Hodges, ; Liryo da Silva, ; Richards, ; Richards & Brown, ; Sheridan, Mittler, Van Gerven, & Covert, ; Whittaker, Davies, & Brown, ) samples proposed that TMJ‐OA is probably associated with dental pathologies as caries and functional overload produced by malocclusal problems derived from dental attrition (DA) and antemortem tooth loss (AMTL) of the posterior dentition. Moreover, some evidence suggested that TMJ‐OA could be also secondary to bruxism, trauma, developmental abnormalities, the morphology of the skull and mandible, and even emotional stress (Bansal, ; Granados, ; Katsavrias, ; Rando & Waldron, ; Richards & Brown, ; Su, Liu, Yang, Shen, & Wang, ; Takayama et al, ; Wang et al, ; Widmalm et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoarthritis can also affect Temporomandibular joint (TMJ) where it involves the cartilage, subchondral bone, and synovial membrane and results in TMJ remodeling and abrasion of articular cartilage [2,3]. Epidemiologic findings of TMJ osteoarthritis are similar to generalized osteoarthritis [4]. The clinical manifestations of TMJ osteoarthritis occurs in 8-16 % of population [5,6]and involvement may be unilateral or bilateral.…”
Section: Introductionmentioning
confidence: 99%